A Pragmatic Analysis and Sociological Perspective on Pearl S Buck’s The Good Earth - Rochmat Budi Santosa (IAIN Salatiga, 2010)
This paper observes the struggle for life of East Asia people that was portrayed in the novel The Good Earth. The Good Earth is also portrayal of a true account experienced by its author, Pearl S Buck. She got inspiration from the life of farmer in China. She wrote this novel using the original name as the main character. Those names are Wang Lung and O Lan. They are couple and their life is on farm. The objectives of this study are to find the pragmatic and sociological aspects of the Novel. This research applies content analysis approach to understand the pragmatic and sociological life in Chinese society, especially in the novel. The finding of the study shows that the utterances in the novel reflect various speech acts i.e. expressive, assertive, commisive, persuasive, directive, and phatic. In the sociological aspect, the life of rural people in Chine is somewhat similar with that of in Indonesia. Otherwise, rural people have life style in common i.e. working hard, struggle for life, defending their belonging, and loving the nature.Keywords: pragmatic analysis; sociological perspective; Good Earth.